DAO voting mechanism resistant to whale and collusion problems - Shunya Tamai; Shoji Kasahara (Frontiers in Blockchain, 2024)
With the widespread adoption of blockchain technology, a novel organizational structure known as Decentralized Autonomous Organizations (DAOs) has attracted considerable attention. DAOs facilitate decision-making through member voting, realizing the governance in a decentralized manner. However, DAOs face unique challenges compared to traditional organization. This paper focuses on two key challenges of governance within DAOs: the whale problem and collusion issue. The whale problem is characterized by the concentration of power among specific members, while for the collusion problem, voting results are distorted by fraudulent collaboration. In terms of voting, we consider Quadratic Voting, a voting system expected to deter the concentration of voting power among a subset of participants, analyzing its resistance to the collusion problem. We show with numerical examples that in comparison to Linear Voting, Quadratic Voting lacks resistance to collusion. Then, we propose a voting mechanism that integrates Quadratic Voting with the Vote escrow tokens, demonstrating the mitigation of the whale problem while acquiring resilience to collusion in the decision-making process. The numerical examples confirm the high efficacy of our proposed model.